Analisis Alur Pelaksanaan Validasi Dokumen Account Receivable & Payable Dalam Shipping Logistic - Fadhil, Ananda M.; Agus Setiono, Beni; Purwiyanto, Didik (Universitas Hang Tuah, 2021)
This study aims to determine the process flow in the validation of Account Receivable & Payable documents from the beginning of the document coming to billing to the vendor at the Inland Service Department (ISD) PT. Salam Pacific Indonesia Lines Surabaya, to find out the things that affect the process of document validation until returning to the branch in implementing shipping logistics. Factors in dealing with document validation problems in the Inland Service Department (ISD) PT. SPIL Surabaya. As well as about handling the problem of incomplete documents and the impact of this happening. The method used in this research is descriptive, where this research refers to problem-solving in a field. The data source used to determine the work process of validating Account Receivable & Payable documents in the Inland Service Department (ISD) is to check documents that come from the branch to proceed to vendor billing, and direct observation. The results of research related to the implementation of the Inland Service Department, officers already have knowledge and skills in dealing with news document validation issues, in carrying out document control that will be sent to the head office at PT. SPIL Surabaya has carried out its duties, responsibilities, and understanding related to the SOP for sending documents well.